PENGARUH RANGSANGAN PUTING SUSU TERHADAP WAKTU KELAHIRAN PLASENTA PADA IBU BERSALIN KALA III DI KLINIK MENTA KECAMATAN PATUMBAK KABUPATEN DELI SERDANG TAHUN 2019 - Andayani Boang Manalu; Puspa Niat Putri Halawa; Nurul Aini Siagian (Jurnal Penelitian Kesmasy, 2019)
Nipple stimulation is an action or treatment given to the nipples in the form of subtle stimulation in the palmar part of the fingers which are carried out alternately which produce the hormone oxytocin naturally, causing the uterus to contract which can prevent postpartum bleeding and accelerate the process of releasing the placenta. This study aims to determine the effect of nipple stimulation on the time of birth of the placenta in the third maternity period. The method used is a quasi-experimental method with a sample of 20 respondents taken by accidental sampling technique. Data analysis using bivariate analysis with t-test independent test statistic. The results showed that the average birth time of placenta in mothers given nipple stimulation was 5.23 minutes, while those not given nipple stimulation 7.02 minutes. Based on the statistical test, it was found that there was an effect of nipple stimulation on the birth time of the placenta in the third stage of maternity with a value of ρ Value 0.002. Suggestions in this study are expected in the management of active management in the third stage to provide stimulation of the nipples to accelerate the birth process of the placenta.